Evaluation of the sound environment of the city of Biskra (Algeria) - Bouzir, Tallal Abdel Karim; Zemmouri, Nourdinne (Journal of Applied Engineering Science & Technology, 2018)
This research concerns the quantitative evaluation of the urban sound environment of the city of Biskra. The aim was to determine the quality of the soundscape based on in situ measurement, using a Landtek SL5868P sound level meter. 62 points have been identified to represent the whole city. The results show that that the noise level varies from 54.1 to 75.8 dB(A) during the weekdays and from 50.4 to 74.2dB(A) during the weekend. In addition,90% of the results of the weekday measurements and 81% of the results of the weekend measurements exceed the recommended levels given by the World Health Organization. The present urban sound exposure could have a substantial impact on the overall comfort of inhabitants and increase the risk of the syndrome of the sick cities.